Plan de negocios para la creación de una empresa de comercialización de calzado y accesorios para mujeres en la ciudad de Guayaquil. - López Murillo, Segundo Alfonso (2012)
This research seeks to know the tastes and preferences of consumers of footwear and accessories for women with the aim of establishing appropriate strategies when creating a company that marketed these products. This research is the result of intensive field work was to conduct direct surveys to potential customers, visiting premises that sell similar products and the interview with artisan producers of these products. The study was based on deductive methods, analytical and statistical. Also using the statistical method consisted of a systematic and organized process was aimed porcentuar, tabular and graph and then analyze and interpret the results related to the different parts of the investigation. Regarding the population was taken as a reference to the inhabitants of the city of Guayaquil, considering gender segmentation and whose age is between 18 and 60 years and is of 652,878 inhabitants, which the survey universe is 390 people. According to the survey analysis allowed us to know that consumers prefer accessories, shoe size used, preferred models, the reason for buying, colors, shape of purchase, etc. The hypothesis is that market research for the creation of the marketing company in footwear and accessories for women can determine wich are the sandals footwear model used by potential consumers. Finally a review of the most relevant literature and web sites of the various institutional actors which established theoretical foundations.